2019
DOI: 10.1007/s10450-019-00047-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bridged monomer on porosity and sorption properties of mesoporous silicas functionalized with diethylenetriamine groups

Abstract: Mesoporous organosilicas functionalized simultaneously with both pendant amine groups and ethylene/phenylene bridges, were synthesized to evaluate the effect of the bridges incorporated in the silica framework on the structure, porosity and adsorption properties of final materials. It turned out that the presence of the bridges enhanced the formation of porosity but adversely affected the efficiency of amination. DFT theoretical calculation showed that the amine groups can be partially bonded by phenyl groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
(82 reference statements)
2
7
0
Order By: Relevance
“…Three diffraction peaks identified at the low Bragg angles of approximately 2θ = 1.0, 2.2, and 3.4° (Figure a) can be indexed as (1 0 0), (1 1 0), and (2 0 0) reflections, respectively. A similar observation was reported by other scholars for the Ca/Si-based materials. ,,, The result confirmed that the Ca/Si-based materials exhibited a high degree of hexagonal mesoscopic structure (2D p 6 mm ). In contrast, a wide peak observed at the range of 2θ = 15–70° (attributed to SiO 2 ) in the wide-angle XRD patterns (Figure b) indicated the typical amorphous structure of the Ca/Si-based materials, which is well-consistent with the literature. ,, Therefore, it can be concluded that the loading process of metals did not significantly affect the original phase structure of the calcium silicate nanoparticles.…”
Section: Resultssupporting
confidence: 90%
“…Three diffraction peaks identified at the low Bragg angles of approximately 2θ = 1.0, 2.2, and 3.4° (Figure a) can be indexed as (1 0 0), (1 1 0), and (2 0 0) reflections, respectively. A similar observation was reported by other scholars for the Ca/Si-based materials. ,,, The result confirmed that the Ca/Si-based materials exhibited a high degree of hexagonal mesoscopic structure (2D p 6 mm ). In contrast, a wide peak observed at the range of 2θ = 15–70° (attributed to SiO 2 ) in the wide-angle XRD patterns (Figure b) indicated the typical amorphous structure of the Ca/Si-based materials, which is well-consistent with the literature. ,, Therefore, it can be concluded that the loading process of metals did not significantly affect the original phase structure of the calcium silicate nanoparticles.…”
Section: Resultssupporting
confidence: 90%
“…% solution of NaCl was used as DICL desorption medium from the loaded samples. Its desorption efficiency was confirmed by us previously in the case of silica materials, where an increase of the ionic strength resulted in significant desorption of DICL [48,49]. The relative desorption efficiencies (RDE) are given in Table 3.…”
Section: The Deconvolution Of O1s Core Energy Level Resulted In Four supporting
confidence: 72%
“…Both the BET surface area closed to 128 m 2 /g and the broad distribution of pores with no clear peak in pore size distribution (Supplementary material 3) suggest almost the non-porous state of pure 100CaP. The N 2 isotherms of parent 100MSi and 10CaP@MSi showed a type IV with a reversible isotherm for MSi and H1-type hysteresis for 10CaP@MSi, corresponded to cylindrical mesopores [29]. For the 20CaP@MSi and 30CaP@MSi, the adsorption isotherms were characterized by two separated steps, corresponding to N 2 condensation in the MSi (at low pressure) and in the CaP domains (at high pressure).…”
Section: Characterization Of Synthesized Cap@msimentioning
confidence: 98%